COGNITIVE BEHAVIOURAL THERAPY TO REDUCE DEPRESSION IN POST STROKE PATIENTS: A SCOPING REVIEW - Dwi Puji Susanti; Niken Safitri Dyan Kusumaningrum; Fitria Handayani (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Post-stroke depression is one of the psychological disorders that is often experienced by post-stroke patients. Depression is more than just sadness. People with post-stroke depression will experience a lack of interest and pleasure in daily activities, weight loss or excessive sleep, lack of energy, inability to concentrate, feelings of worthlessness or guilt and recurring thoughts of death or suicide. Based on several types of post-stroke depression management, psychosocial interventions have been shown to reduce the likelihood of developing post-stroke depression. One of the interventions to reduce post-stroke depression is cognitive behavioral therapy. Objective: This scoping review aims to identify the effectiveness of cognitive behavioral therapy to reduce depression in post-stroke patients. Design: This study used a scoping review through a review of articles on cognitive behavioral therapy that has been used to reduce depression in post-stroke patients. Data Sources: Search for articles accessed through a database, including: CINAHL, MEDLINE, Academic search ultimate, PubMed, and google scholar with a range of search years 2011-2020. Review Methods: Quality appraisal assessment for each selected study was conducted using the Preferred Reporting Items for scoping review (PRISMA) method. Results: The results of this literature review show that cognitive behavioral therapy to reduce depression in post-stroke patients can change thoughts, feelings and behaviors to influence each other. The relationship between thoughts, feelings and behavior greatly influences respondents in dealing with post-stroke conditions with a positive way of thinking so that it will accelerate or help the post-stroke recovery process. The way to implement cognitive behavioral therapy is to be given as many as 12 sessions in 25-35 minutes each session. Cognitive behavioral therapy can be done in a hospital and has a significant post-stroke depression rate with p <0.01. Conclusion: Cognitive behavioral therapy can be given as an intervention to reduce depression in post-stroke patients including cognitive behavioral therapy, duration of cognitive behavioral therapy and sessions in cognitive behavioral therapy.